Regenerative Brake System for Small Scale Electric Bus - Ferreira, T. J. P. [UNESP]; Melo, G. A. [UNESP]; Canesin, C. A. [UNESP]; Brito, M. A. G.; IEEE (Ieee, 2014)
This paper proposes a regenerative braking system for a small-scale prototype applied to an electric bus, which is driven by a DC motor. The employed topology is based on two bidirectional DC-DC converters, cascaded connected, and with specific energy control function to provide energy flux between accumulators and motor drive. The recovered energy provided for the traction motor, when operating as a generator, is stored in a supercapacitor pack, which can feed the Li-Ion battery packs, depending on their charge conditions. Using MatLab-Simulink integrated to a DSpace platform for the control logic development, a prototype was designed for practical investigation. Finally, it should be informed that the experimental results from this prototype will be presented in a future paper.